Significantly Increased Lightning Activity Over the Tibetan Plateau and Its Relation to Thunderstorm Genesis. Issue 16 (19th August 2022) - Qie, Xiushu; Qie, Kai; Wei, Lei; Zhu, Kexin; Sun, Zhuling; Yuan, Shanfeng; Jiang, Rubin; Zhang, Hongbo; Xu, Chen
Abstract: Under the context of global warming, we identified a significant increase in lightning activity in the last two decades over the Tibetan Plateau (TP), the highest plateau on earth, based on two data sets. The largest rise of lightning activity was found over the region with high lightning density represented by the eastern TP at a rate of 0.072 ± 0.069 fl km −2 yr −1 during 1996–2013 from Optical Transient Detector/Lightning Imaging Sensor. World Wide Lightning Location Network data also showed a remarkable increase in lightning strokes during 2010–2019 in the maximum lightning density region, while the change was insignificant in the low lightning density region. Further investigations revealed that most of the TP region experienced a significant increase in thunderstorm frequency, which was responsible for the increase in lightning activity, rather than an increase in thunderstorm intensity. Increased lightning activity implies a potential risk to human beings and the fragile ecosystem over the TP in a warmer climate. Plain Language Summary: Lightning is a natural source of nitrogen oxides and wildfires, and thus has important effects on atmospheric chemistry and ecosystem. Lightning is also a serious threat to human life and property. Using satellite‐based and ground‐based data, the trend of lightning activity over the Tibetan Plateau (TP) in the past two decades has been investigated in this paper. In the global warming context, TP experienced an increase in lightning activity. The lightning increase was significant in the high lightning density region, such as the central and eastern TP, and insignificant in the lower lightning density region, such as the western TP and the Brahmaputra Valley. The thunderstorm frequency also experienced an increase over most parts of the TP, which caused the rising trend in lightning activity. However, the thunderstorm intensity shows weak and insignificant changes. Since the TP is getting warmer much faster than that observed over the globe, the increased lightning activity over the TP may exert enhanced potential threat to human beings and impacts on the fragile ecosystem over the Plateau. Key Points: Lightning activity over the Tibetan Plateau increased significantly in the past two decades based on the Optical Transient Detector/Lightning Imaging Sensor and World Wide Lightning Location Network datasets Lightning activity in the high‐flash‐density region increased faster than that in the low‐flash‐density region The apparent rise in lightning activity is due to increase in thunderstorm rate rather than change in thunderstorm intensity